Motivating Prosocial Venturing in Response to a Humanitarian Crisis: Building Theory From the Refugee Crisis in Germany. (May 2023) - Mittermaier, Alexandra; Patzelt, Holger; Shepherd, Dean A.
In the context of the humanitarian refugee crisis in Germany, we conducted an 8-month qualitative study of prosocial ventures that emerged during this crisis to build a theory of motivation in prosocial venturing. We identified two venturing paths driven by founders' distinct motivations. Founders motivated by others' suffering focused on rescuing refugees, following an execution-oriented approach, and scaling their activities to meet victims' short-run needs. Founders motivated by entrepreneurial aspirations focused on building an organization, following a foundation-oriented approach, and customizing activities to meet victims' long-run needs. This study contributes to prosocial venturing and crisis research.